Kinetic of fermentation and antimicrobial activity of Weissella confusa against Staphylococcus aureus and Streptococcus agalactiae - Liliana Serna Cock; Leidy Johana Valencia Hernández; Rómulo Campos Gaona (Revista Facultad de Ingeniería Universidad de Antioquia, 2013)
The kinetics of biomass and lactic acid production, substrate consumption, antimicrobial activity of Weissella confusa, a lactic acid bacteria with antimicrobial activity against Streptococcus agalactiae and Staphylococcus aureus, bovine-mastitis producing microorganisms, were evaluated. The fermentations were carried out anaerobically in batch using as substrate, commercial substrate (SC), milk supplemented with yeast extract (LEL) and milk supplemented with yeast extract and glucose (LELG) and the kinetic parameters were compared. The greater the inhibition of pathogens, the greater production of lactic acid and the higher yield of biomass is presented on substrate LELG. This substrate presented a diameter of inhibition of 36.33 mm for Staphylococcus aureus after the fourth hour of fermentation and 39 mm of diameter for Streptococcus agalactiae at the eighth hour of fermentation; maximum production of lactic acid was 13.12 gL-1 (at 48 h) and maximum concentration of biomass was 3.07 gL-1 (at 48 h). These results were superior to those obtained on SC where, for the same fermentation time 24.38 mm for Staphylococcus aureus and 30.58 mm diameter of inhibition for Streptococcus agalactiae were obtained; the highest lactic acid production was 11,6 gL-1 (at 12h) and the highest concentration of biomass was 1.18 gL-1(at 24 h). The results suggest that LELG may become a low cost alternative for the production of Weissella confusa, microorganism with great potential for control and treatment of bovine mastitis.